STRATEGIC CHARITY IMPLEMENTATION IN INDONESIA’S RURAL ISLAMIC FINANCIAL INSTITUTION - Devi Ayu Kurniati; Agung Guritno (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2019)
Strategic Charity, as the more specific implementation of Corporate Social Responsibility (CSR), is now gained its popularity among the company in Indonesia, including the Islamic Financial Institution. However, the execution sometimes did not achieve the goal nor misdirected. This study was conducted to determine the implementation of strategic charity done by BMT Al-Hikmah, Ungaran, Central Java. The method used was qualitative descriptive, and data collection was done using interviews and observations. The study revealed that the source of funds of the strategic charity comes from zakat, infaq, alms, and fines fund. The implementation was right on the target even though sometimes it is not enough since the source of funds is minimal while so many parties need those funds.